An evaluation of serum boron level in pregnancies with severe pre-eclampsia - Tok Abdullah; Özer Serdar; Özer Alev; Kaplanoğlu Dilek; Arıkan Tuğba (Türk Biyokimya Dergisi)
Serum boron level has not been studied in pregnancies with pre-eclampsia. The aim of this study was to compare the levels of serum boron in pregnancies with early onset severe pre-eclampsia and healthy pregnancies.